Perkawinan yang Berkenan: Kajian Hermeneutik Kritik Historis Berdasarkan 1 Korintus 7:1-16 dan Implikasinya Bagi Jemaat - Sangian, Eiffel; Tewu, Peggy Sandra (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2024)
This article is about marriage and divorce. This letter was written by Paul to the church in Corinth. Paul emphasized the importance of maintaining the sanctity of marriage and avoiding fornication. He also offered a solution for married couples to stay away from each other by mutual consent for a while, in case of problems in their marriage. Paul reminds us that divorce is not a way out. The article entitled